Editorial Thematic Section: Youth, work and inequalities - Guillermo Rivera-Aguilera; Escuela de Psicología, Pontificia Universidad Católica de Valparaíso; Manuela García Quiroga; Escuela de Psicología Pontificia Universidad Católica de Valparaíso; Oscar López Cortés; Lorena Pérez-Roa; Universidad de Chile; Ludmila Costhek Abilio (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
The transformations of work in recent decades have had strong repercussions on the youth population. The increase in unemployment, the flexibilization of work, the promotion of entrepreneurship and the consolidation of neoliberalism significantly affect young people. The problem of youth unemployment has traditionally been associated with poor and developing countries; however, in recent years we have witnessed how this phenomenon also strongly affects the most advanced economies of the planet. Official data from the International Labour Organization indicate that 70.9 million young people between the ages of 15 and 24 are currently unemployed, the majority of whom are women. This Thematic Section is made up of a total of nine articles selected from a total of 26 manuscripts received. The works presented address diverse topics, among them we have: a) debt and youth, b) precarization of work and entrepreneurship policies, c) uberization of work, d) Ni-Nis and inclusion in the world of work, and e) educational trajectories.